Digitalization Of Tax Administration Systems And Tax Complience Costs On Taxpayer Complience Of Individual Taxpayer : Digitalisasi Sistem Administrasi Perpajakan Dan Biaya Kepatuhan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Wulandari, Dian Sulistyorini (Journal of Accounting Science, 2021)
This study aims to examine the effect of the application of e-filing, e-billing, e-invoicing, and tax compliance costs on taxpayer compliance. The independent variable in this research are e-filing, e-billing, e-invoicing, and tax compliance, while dependent variabe is taxpayer compliance. The population in this research was an individual taxpayer listed in KPP Pratama South Cikarang. The sample in this study is determined by random sampling method with a sample size of 100 respondents. the primary data collectin method used in this study is a survey method with questionnaire media. The method of analysis used is multiple linear regression. The results of this research is shows that the effect of the application of e-filling and e-invoicing has a positif effect on taxpayer compliance. Tax compliance cost have a negative effect on taxpayer compliance. While the effect of the application of the e-billing has no effect on taxpayer compliance.